2014
DOI: 10.4319/lo.2014.59.4.1388
|View full text |Cite
|
Sign up to set email alerts
|

A feedback loop links brownification and anoxia in a temperate, shallow lake

Abstract: This study examines a natural, rapid, fivefold increase in dissolved organic carbon (DOC) concentrations in a temperate shallow lake, describing the processes by which increased DOC resulted in anoxic conditions and altered existing carbon cycling pathways. High precipitation for two consecutive years led to rising water levels and the flooding of adjacent degraded peatlands. Leaching from the flooded soils provided an initial increase in DOC concentrations (from a 2010 mean of 12 6 1 mg L 21 to a maximum conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
143
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(153 citation statements)
references
References 42 publications
(61 reference statements)
5
143
1
1
Order By: Relevance
“…To date there have been four whole-lake studies on the effects of increased DOC concentration on lake ecosystem processes. However, two of the studies involved extreme and rapid changes in DOC concentrations unlike those that have been observed in most natural systems (Sadro and Melack 2012;Brothers et al 2014), another study added DOC in the form of sucrose, which is much more labile and less chromophoric than natural DOC (Blomqvist et al 2001), and the fourth study unexpectedly observed an increase in DOC concentration that confounded a nutrient and food-web structure manipulation experiment (Christensen et al 1996). In this study, we induced an increase in DOC concentration, using a natural source, by a magnitude consistent with observed longterm trends (Monteith et al 2007) in one basin of an experimental lake to examine the physiochemical and basal metabolic responses of a lake under elevated DOC concentration.…”
Section: Discussionmentioning
confidence: 99%
“…To date there have been four whole-lake studies on the effects of increased DOC concentration on lake ecosystem processes. However, two of the studies involved extreme and rapid changes in DOC concentrations unlike those that have been observed in most natural systems (Sadro and Melack 2012;Brothers et al 2014), another study added DOC in the form of sucrose, which is much more labile and less chromophoric than natural DOC (Blomqvist et al 2001), and the fourth study unexpectedly observed an increase in DOC concentration that confounded a nutrient and food-web structure manipulation experiment (Christensen et al 1996). In this study, we induced an increase in DOC concentration, using a natural source, by a magnitude consistent with observed longterm trends (Monteith et al 2007) in one basin of an experimental lake to examine the physiochemical and basal metabolic responses of a lake under elevated DOC concentration.…”
Section: Discussionmentioning
confidence: 99%
“…While the cause of this browning trend remains to be determined, it has been hypothesized that elevated temperatures, altered hydrology, land-use change, or reduced acid deposition may be contributing to the increased flux of DOC from terrestrial to aquatic ecosystems (Garnett et al 2000, Roulet and Moore 2006, Monteith et al 2007). Far less attention, however, has focused on the consequences of this widespread environmental change for recipient aquatic ecosystems and the stability of the ecosystem services they provide (Brothers et al 2014;Solomon et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These bacteria can strive in anoxic zones of DOC rich lakes that resulting from light attenuation [81, 82]. Furthermore, we found a significant correlation of DOC and a number of fatty acids that we pooled into the group of bacterial fatty acids in pelagic phenotypes (S1 Fig).…”
Section: Discussionmentioning
confidence: 83%